Ethical Codes and Ethical Control in the Social Sciences - Klaus Mäkelä (Suomen Antropologi, 2008)
This report discusses the colonial heritage and changes in the social position of anthropologists as reflected in the code of ethics of the American Anthropological Association (AAA). It describes changes in the Association’s ethical guidelines since 1948 and interprets them as reflections of changes in the social position of anthropologists. It is the opinion of the author that the early statements and codes describe the ethical anthropologist as an independent champion of truth. Later codes describe the ethical anthropologist as one who complies with legal regulations and fulfilling his or her contractual obligations towards the employer, sponsor, or client. The author suggests that these changes should also be seen against the background of the position of American anthropologists in the labour market. In the 1960s, the great majority of anthropologists were academics. From 1986 onwards, the majority were working outside of academia.